Changes in lung sialidases in male and female mice after bleomycin aspiration. (1st December 2022) - Pilling, Darrell; Sahlberg, Kyle; Chen, Wensheng; Gomer, Richard H.
ABSTRACT: Aim of the study: Sialidases, also called neuraminidases, are enzymes that cleave terminal sialic acids from glycoconjugates. In humans and mice, lung fibrosis is associated with desialylation of glycoconjugates and upregulation of sialidases. There are four mammalian sialidases, and it is unclear when the four mammalian sialidases are elevated over the course of inflammatory and fibrotic responses, whether tissue resident and inflammatory cells express different sialidases, and if sialidases are differentially expressed in male and females. Materials and Methods: To determine the time course of sialidase expression and the identity of sialidase expressing cells, we used the bleomycin model of pulmonary fibrosis in mice to examine levels of sialidases during inflammation (days 3 − 10) and fibrosis (days 10 − 21). Results: Bleomycin aspiration increased sialidase NEU1 at days 14 and 21 in male mice and day 10 in female mice. NEU2 levels increased at day 7 in male and day 10 in female mice. NEU3 appears to have a biphasic response in male mice with increased levels at day 7 and then at days 14 and 21, whereas in female mice NEU3 levels increased over 21 days. In control mice, the sialidases were mainly expressed by EpCAM positive epithelial cells, but after bleomycin, epithelial cells, CD45 positive immune cells, and alveolar cells expressed NEU1, NEU2, and NEU3. Sialidase expression was higher in male compared to female mice. There was little expression of NEU4 in murine lung tissue. Conclusions: These results suggest that sialidases are dynamically expressed following bleomycin, that sialidases are differentially expressed in male and females, and that of the four sialidases only NEU3 upregulation is associated with fibrosis in both male and female mice.